PEMBERDAYAAN PEMUDA DALAM PROGRAM KOTA LAYAK PEMUDA (KLP) DI KOTA PEKANBARU - Utami, Indah Restu; SD, Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pekanbaru is the capital city of Riau Province, which is one of the centers of economic growth and trade, a city with a high population growth rate and is one of the destinations for population movement from villages to cities. Pekanbaru as one of the cities that has a large population in Indonesia with the majority of the population aged 15-29 years who are classified as youth. With a large number of youth in Pekanbaru, Pekanbaru City youth have a high interest in participating and forming youth organizations and have succeeded in creating environmental care applications that can make Pekanbaru City win an award as a youth-worthy city in 2019. The purpose of this study is to find out youth empowerment in the youth decent city program (KLP) in Pekanbaru City and knowing the supporting factors for youth empowerment in the youth decent city program (KLP) in Pekanbaru City. This study uses a snow ball sampling technique with a qualitative research type with a phenomenological approach. The collection of both primary and secondary data obtained through interviews, observation and documentation and then analyzed based on research problems. The results showed that youth empowerment in the youth decent city program (KLP) in Pekanbaru City was still less than optimal, due to several indicators that were still not running well. namely the will and role of good government.Â Keywords: Empowerment,City Worth Youth, PekanbaruÂ